2022
DOI: 10.1039/d2en00148a
|View full text |Cite
|
Sign up to set email alerts
|

Nanoconfinement matters in humidified CO2 interaction with metal silicates

Abstract: With enigmatic observations of enhanced reactivity of wet CO2-rich fluids with metal silicates, the mechanistic understanding of molecular processes governing carbonation proves critical in designing secure geological carbon sequestration and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 124 publications
(173 reference statements)
0
4
0
Order By: Relevance
“…ref. 14 and 16-18) the most attention of any mineral for carbon storage reactivity, due to its rapid carbonation kinetics, 17,[19][20][21][22][23][24][25] structural and chemical simplicity, along with its prevalence in ultramafic rocks and many basalt formations. In contrast, relatively little mineral carbonation research has been conducted on more abundant and widespread minerals that have more complex structures and compositions.…”
Section: Introductionmentioning
confidence: 99%
“…ref. 14 and 16-18) the most attention of any mineral for carbon storage reactivity, due to its rapid carbonation kinetics, 17,[19][20][21][22][23][24][25] structural and chemical simplicity, along with its prevalence in ultramafic rocks and many basalt formations. In contrast, relatively little mineral carbonation research has been conducted on more abundant and widespread minerals that have more complex structures and compositions.…”
Section: Introductionmentioning
confidence: 99%
“…Carbonic acid or bicarbonate ion generation has been identified by molecular dynamic studies. 59,60 The 29 Si NMR result demonstrated that Q 3 was the dominant coordination for sample SGRH55−24 h, during which the CH was not depleted as shown in the XRD result, whereas C−S−H started to decalcify in water-rich carbonation only when the CH was depleted. The presence of CH and decalcification of C−S−H led to an alkaline pore solution with a high calcium concentration.…”
Section: Ion Concentration Evolutionmentioning
confidence: 86%
“…Based on eq and with an RH of 55% (in the case of this study), nanosized pores of around 4 nm were saturated, which meant that only thin water films were present in RCPs. , Unlike the solution-precipitation process, a nanometer-thick water film on the inner or outer surfaces of RCPs would provide a low energy barrier for CO 2 dissolution. Carbonic acid or bicarbonate ion generation has been identified by molecular dynamic studies. , The 29 Si NMR result demonstrated that Q 3 was the dominant coordination for sample SGRH55–24 h, during which the CH was not depleted as shown in the XRD result, whereas C–S–H started to decalcify in water-rich carbonation only when the CH was depleted. The presence of CH and decalcification of C–S–H led to an alkaline pore solution with a high calcium concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Extending the notion of bond order parameters in modeling covalent systems, [24] reactive force fields, such as ReaxFF [25] and AIREBO, [26] provide a classical compromise with DFT-level accuracy and accelerate calculations by orders of magnitude. Properly parameterized ReaxFF potentials can simulate chemical reactions at the solid, liquid, and gas interfaces and these potentials have already advanced our understanding of a range of complex geochemical reactions from interfacial carbon mineralization [27][28][29] to the maturation of organic matter. [30,31] Previously, we developed an H/C/O/Cl ReaxFF potential [32] to model the oxidation of organic matter with oxychlorine reagents, which remain limited to very low pH due to the absence of alkaline or earth alkaline cations in the parameter set to balance the charged reactive fluid.…”
Section: Introductionmentioning
confidence: 99%